Hubungan Pengetahuan dan Sikap dengan Prilaku Pencegahan Penyakit Malaria - Rismawati muhadi; Erna Melastuti; Indah Sri Wahyuningsih (STIKes Ibnu Sina Ajibarang, 2025)
Malaria is an infectious disease caused by various species of Plasmodium, such as Plasmodium vivax, Plasmodium falciparum, Plasmodium malariae, and Plasmodium ovale, which are transmitted through the bite of Anopheles mosquitoes. The spread of this disease is highly influenced by the presence of mosquito breeding sites as vectors of transmission. This study aims to analyze the relationship between the knowledge and attitudes of outpatients toward malaria prevention behaviors at the ASA Enterop Clinic in Jayapura. The study design used a descriptive analytical method with a cross-sectional approach. The research instrument was a questionnaire, and data analysis involved both univariate and bivariate analysis, as well as Chi-square statistical testing. The results showed that 57 respondents (54.0%) had good knowledge with good prevention behavior, and 5 respondents (8.0%) had moderate knowledge with good prevention behavior. Meanwhile, 1 respondent (4.4%) had good knowledge but poor prevention behavior, and 5 respondents (5.0%) had moderate knowledge with poor prevention behavior. The conclusion of this study indicates a significant relationship between knowledge and attitudes with malaria prevention behavior in the research area. These findings highlight the importance of improving public knowledge and attitudes in preventing malaria and suggest that strengthening health education and awareness is crucial for disease prevention.